Breeding Strategies for Lodging Resistance in Rice - M., Girija Rani; P. V., Satyanarayana; M., Lal Ahmed; Y., Ashok Rani; V., Srinivasa Rao; P, Jhansirani (International Journal of Bio-resource and Stress Management, 2017)
Lodging of the rice crop is the major limiting factor to rice productivity in cyclone prone areas. Lodging not only reduces the yield but also it deteriorates grain quality impedes mechanical harvesting, increases harvesting and drying costs. Lodging resistance is complex trait influenced by environment and structural properties of the stem. Factors like cultivar, fertilizers application, irrigation, plant density, pest and disease management influences lodging apart from weather parameters. Though semi dwarf gene reduced lodging to certain extent but it resulted in yield plateau and also high yielding semi dwarf rice varieties like Swarna prone to lodging because of weak culm. Breeding for lodging resistant rice varieties is important strategy to combat adverse effects of climatic changed conditions. Direct selection for lodging resistance by visual score in segregating material is herculean task as it is influenced by structural properties of the stem and weather parameters. Type of lodging decides selection of traits suitable for lodging resistance. Stem lodging is the main type of lodging limits the rice productivity in irrigated ecosystem. This review focused on understanding the problems of lodging, effects of lodging, factors influencing lodging resistance, physiological basis of lodging, breeding for lodging resistance and Quantitative trait loci (QTLs) associated with lodging resistance related traits. Root lodging prevails under direct seeded condition where root anchorage is poor. Selection suitable phenotypic traits and genotyping with suitable molecular markers would help in framing suitable breeding strategy for the development of lodging resistant rice varieties.